Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{\left(\sqrt{2}+\sqrt{3}+\sqrt{6}\right)\left(2\sqrt{6}+1\right)}{23}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(\sqrt{18}-\frac{1}{3}\sqrt{72}-\sqrt{8}+\frac{2-3\sqrt{2}}{3-\sqrt{2}}\)
\(=3\sqrt{2}-\frac{6\sqrt{2}}{3}-2\sqrt{2}+\frac{\left(3+\sqrt{2}\right)\left(2-3\sqrt{2}\right)}{9-2}\)
\(=3\sqrt{2}-2\sqrt{2}-2\sqrt{2}-\sqrt{2}\)
\(=-2\sqrt{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{5}{2+\sqrt{3}}=\frac{5\left(2-\sqrt{3}\right)}{\left(2+\sqrt{3}\right)\left(2-\sqrt{3}\right)}=\frac{5\left(2-\sqrt{3}\right)}{4-3}=5\left(2-\sqrt{3}\right)\)
\(\frac{5}{\sqrt{5}}=\frac{5\sqrt{5}}{\sqrt{5}.\sqrt{5}}\frac{5\sqrt{5}}{5}=\sqrt{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\left(\sqrt{2006}-\sqrt{2005}\right).\left(\sqrt{2006}+\sqrt{2005}\right)=\left(2006-2005\right)=1\)
b.
=\(\frac{7+4\sqrt{3}+14-8\sqrt{3}}{49-48}\left(21+4\sqrt{3}\right)\)
=\(\left(21-4\sqrt{3}\right)\left(21+4\sqrt{3}\right)\)
=441-48
393
vậy.......
hc tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
f: \(\dfrac{2}{\sqrt{6}-\sqrt{5}}=2\sqrt{6}+2\sqrt{5}\)
l: \(\dfrac{3}{\sqrt{10}+\sqrt{7}}=\sqrt{10}-\sqrt{7}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=\frac{\left(\sqrt{x}-\sqrt{4y}\right)\left(\sqrt{x}-\sqrt{y}\right)}{\left(\sqrt{x}+\sqrt{y}\right).\left(\sqrt{x}-\sqrt{y}\right)}+\frac{3x.\left(x-\sqrt{xy}\right)}{\left(x+\sqrt{xy}\right).\left(x-\sqrt{xy}\right)}\)
\(=\frac{\left(\sqrt{x}-2.\sqrt{y}\right).\left(\sqrt{x}-\sqrt{y}\right)}{x-y}+\frac{3x.\sqrt{x}.\left(\sqrt{x}-\sqrt{y}\right)}{x^2-xy}\)
\(=\frac{\left(\sqrt{x}-2.\sqrt{y}\right).\left(\sqrt{x}-\sqrt{y}\right)}{x-y}+\frac{3x\sqrt{x}.\left(\sqrt{x}-\sqrt{y}\right)}{x.\left(x-y\right)}\)
\(=\frac{\left(\sqrt{x}-2.\sqrt{y}\right).\left(\sqrt{x}-\sqrt{y}\right)}{x-y}+\frac{3\sqrt{x}.\left(\sqrt{x}-\sqrt{y}\right)}{x-y}\)
\(=\frac{\left(\sqrt{x}-2.\sqrt{y}\right).\left(\sqrt{x}-\sqrt{y}\right)+3.\sqrt{x}.\left(\sqrt{x}-\sqrt{y}\right)}{x-y}\)
\(=\frac{\left(\sqrt{x}-\sqrt{y}\right).\left(\sqrt{x}-2.\sqrt{y}+3.\sqrt{y}\right)}{\left(\sqrt{x}-\sqrt{y}\right).\left(\sqrt{x}+\sqrt{y}\right)}\)
\(=\frac{\left(\sqrt{x}-\sqrt{y}\right).\left(\sqrt{x}+\sqrt{y}\right)}{\left(\sqrt{x}-\sqrt{y}\right).\left(\sqrt{x}+\sqrt{y}\right)}\)
\(=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Thêm câu này hộ tớ nx nhé !
e) \(\left(\sqrt{8}-3\sqrt{2}+\sqrt{10}\right).\left(\sqrt{2}-3\sqrt{0.4}\right)\)
\(a,\left(\frac{2\sqrt{3}-\sqrt{6}}{\sqrt{8}-2}-\frac{\sqrt{216}}{3}\right)\cdot\frac{1}{\sqrt{6}}\)
\(=\left(\frac{\sqrt{12}-\sqrt{6}}{2\left(\sqrt{2}-1\right)}-\frac{6\sqrt{6}}{3}\right)\cdot\frac{1}{\sqrt{6}}\)
\(=\left(\frac{\sqrt{6}\left(\sqrt{2}-1\right)}{2\left(\sqrt{2}-1\right)}-2\sqrt{6}\right)\cdot\frac{1}{\sqrt{6}}\)
\(=\left(\frac{\sqrt{6}}{2}-\frac{4\sqrt{6}}{2}\right)\cdot\frac{1}{\sqrt{6}}\)
\(=\frac{\sqrt{6}-4\sqrt{6}}{2}\cdot\frac{1}{\sqrt{6}}\)
\(=\frac{-3\sqrt{6}}{2}\cdot\frac{1}{\sqrt{6}}\)
\(=-\frac{3}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có: \(\left(\sqrt{8}-3\sqrt{2}+\sqrt{10}\right)\sqrt{2}-\sqrt{5}\)
\(=\left(-\sqrt{2}+\sqrt{10}\right)\sqrt{2}-\sqrt{5}\)
\(=-2+2\sqrt{5}-\sqrt{5}\)
\(=-2+\sqrt{5}\)
b) \(\left(\frac{1}{2}\sqrt{\frac{1}{2}}-\frac{3}{2}\sqrt{2}+\frac{4}{5}\sqrt{200}\right)\div\frac{1}{8}\)
\(=\left(\frac{\sqrt{2}}{4}-\frac{3\sqrt{2}}{2}+8\sqrt{2}\right)\cdot8\)
\(=\frac{27\sqrt{2}}{4}\cdot8\)
\(=54\sqrt{2}\)